Indigo - Balbarez, Ace Meelan Mabilangan; Deocampo, Nicolas Francisco (Quezon City College of Mass Communication, University of the Philippines, 2023)
Indigo, a stuttering college student, finds a magic cubicle that transports him back in time. Upon abusing this power to improve his speech condition, Indigo gets lost in time and experiences the history of student activism in the university from the 2000s to the 1970s. This film aims to rediscover and reclaim our narrative given our country's present political situation—another Marcos regime—that is beset with historical revisionism. This production thesis embodies cinema, as a mode of representation, to address misrepresentation as in the case of historical distortion and underrepresentation as in the case of people with disabilities. In this postmodern age that gave rise to post-truth in media, Indigo blurs the line and recognizes the parallelism between past and present through time travel. Indigo is a caricature of the youth whose individual subjectivity is challenged to move from personal to political perspectives. Essentially, this project aims for media representation and serves as a reminder of an important national memory—one that is ever relevant in the university—the Diliman Commune. The short film wishes for the audience to remember the forgotten past that should haunt the present generation, represented by the character of Indigo.
Vita.
Thesis
Includes bibliographical references (page 123-129) and appendices (pages 147-199).
Keywords: Martial law -- Philippines; Student movements -- Philippines; Time travel; Short films